Non-linear resistance training program induced power and strength but not linear sprint velocity and agility gains in young soccer players - Barbalho, M.; Gentil, P.; Raiol, R.; Boscolo del Vecchio, F.; Ramirez-Campillo, R.; Silveira Coswig, V. (Sports, 2018)
Background: The present study evaluated the effects of resistance training (RT) following a non-linear periodization model in the physical fitness of young soccer athletes. Methods: Young soccer players (n = 23) were allocated into two groups: an RT group (RTG), and the control group (CON). The RTG underwent 15 weeks of non-linear RT periodization in three weekly sessions in addition to their specific soccer training. The CON continued performing the specific soccer training. Before and after the training period, all of the subjects performed one-repetition maximum (RM) tests for speed, agility, and power (vertical and horizontal jump). Results: The RTG obtained significant gains in one-RM tests (before 64.1 ± 5.8 kg, after 79.1 ± 3.3 kg) and power (vertical jump (before 56 ± 2.7 cm, after 61.3 ± 1.7 cm) and horizontal jump (before 184.5 ± 5.5 cm, after 213.6 ± 3.2 cm)). In contrast, the CON group presented a non-significant increase in one-RM tests and horizontal jump, and a significant reduction in vertical jump (before 55.4 ± 2.2 cm, after 51.3 ± 1.5 cm). Neither group presented significant gains in speed (CON: p = 0.27; RTG: p = 0.72) and agility (CON: p = 0.19; RTG: p = 0.58). Conclusion: Our data suggest that non-linear RT should be inserted into the routine of young soccer athletes for improving strength and power without impairing speed and agility.